Nursing care systems and complex thought in nursing education: document analysis - Josilaine Porfírio da Silva; Mara Lucia Garanhani; Maria Helena Dantas de Menezes Guariente
The aim of this study was to analyse the inclusion of the subject Nursing Care Systems (NCS) in nursing education. This study was based on qualitative desk research and it was conducted in a nursing programme in southern Brazil that offers an integrated curriculum with NCS as a cross-cutting theme. Data were collected from September to December 2012, by examining 15 planning and development workbooks on the cross-disciplinary modules of the programme. Analysis was divided into four stages: exploratory, selective, analytic and interpretive reading. The adopted theoretical framework was Complex Thought of Edgar Morin, according to the principles of relevant knowledge. Results were arranged into two categories: NCS as a crosscutting theme in nursing education: the context, the global and the multidimensional; and strategies for teaching, learning and assessment of NCS: the complex. The study contributes to the debate on the importance of teaching NCS as a crosscutting theme in nursing education.